Investigation of particle exhaust from EAST divertor. (October 2022) - Cao, B.; Wang, L.; Yu, Y.W.; Zuo, G.Z.; Hu, J.S.
Highlights: The plasma density decay time during all fueling shut off was used as a gauge to evaluate the performance of the divertor particle exhaust. The helium particle exhaust performance of EAST upper tungsten divertor and the particle exhaust capability of new lower tungsten divertor have been investigated. Abstract: Particle control is one of the key issues for steady-state tokamak operation. The density decay time is used to evaluate the capability of the divertor to exhaust particle with all fueling turn off. Experiments of the EAST divertor's ability to exhaust helium particles were also performed during the EAST helium plasma operation. The experimental results show that the EAST divertor is less capable of exhaust helium particles than deuterium particles. And similar to deuterium, the helium particle exhaust performance is sensitivity on the different strike point location. During 2021 experiment campaign, a new lower tungsten divertor has been developed and installed on EAST, the particle exhaust capacity of the new divertor has also been investigated during this campaign.